Meningkatkan Kualitas Pendidikan Anak Panti Asuhan Melalui Bimbingan Belajar Berbasis Teknologi di Panti Asuhan Menara Kasih Indonesia - Akbar, Arairis (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This Pkl 1 program uses the casework method as an individual intervention approach to improve the learning abilities of children at the Menara Kasih Indonesia Orphanage in Medan City. The process is carried out through six stages: involvement, assessment, planning, intervention, evaluation, and termination. The results of the activity showed a significant increase in academic aspects, mastery of technology, and learning attitudes, the ability to use the courage application, and social engagement. Major obstacles such as limited devices and internet connections were overcome through flexible approaches such as rotating learning and shared hotspots. Emotional guidance has consistently been shown to be able to trigger behavioral transformation that has long-term impacts. The casework method shows effectiveness in handling educational cases in limited social environments, and is recommended as an alternative approach to strengthening the learning of children in orphanages